BUILDING A CULTURE OF RESEARCH: FOCUS GROUP DISCUSSION - Malik, Samina; Mahmud, Qanita; Janjua, Qasim M.; Saeed, Saman; Al-Eraky, Mohamed M. (Pakistan Journal of Physiology, 2017)
Background: Medical curriculum should be enabled to train students in research but focus in this regard is much lacking. This study was designed to explore the perception of final year medical students regarding pre-requisites of a research culture at the level of institute, faculty and leadership. Methods: A focus group discussion with two mini groups (male and female group), each consisting of 6 members and supervised by an experienced moderator was conducted. The study comprised of discussion lasting for 90 minutes. Firstly, opinions of students were gathered and coded, then it was followed by conversion of their statements into themes and interpretation of results. Results: Discussion on institutional factors, role of faculty and importance of leadership was carried out and numerous themes were identified. Among institutional factors, themes of curriculum & funding were revealed. Regarding the role of faculty, themes of motivation, skill learning & mentor-mentee ratio were highlighted and while discussing the fundamental role of leadership, need of a role model, who must be a flexible leader was emphasized. Conclusion: Institutes should support a curriculum with early exposure to research, along with hiring of supportive, research oriented faculty who can prove to be the role model & flexible research leader. Pak J Physiol 2017;13(4):45–7